2022
DOI: 10.7759/cureus.22461
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Evaluation by Telephone and Video Visit: A Narrative Review

Abstract: Telemedicine has a very important role in today's healthcare system, which has been accentuated during the SARS-CoV-2 pandemic. Virtual medical evaluations offer a myriad of benefits for both patients and providers. Evaluations of the musculoskeletal system, however, present unique challenges because diagnosis significantly relies on a physical examination, something not easily accomplished by virtual means. The shoulder, a complex region with four separate articulations, is no exception. Nevertheless, a prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Our protocol appears to be in line with other methodologies used in other studies [40]. However, the use of everyday objects is promoted in our study to be able to quantify functional shoulder deficits and to standardize patient assessment and follow-up as much as possible.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our protocol appears to be in line with other methodologies used in other studies [40]. However, the use of everyday objects is promoted in our study to be able to quantify functional shoulder deficits and to standardize patient assessment and follow-up as much as possible.…”
Section: Discussionmentioning
confidence: 85%
“…Other recent studies have shown that in-person clinical examination is necessary to confirm suspected instability of the shoulder [39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%